Pelatihan Literasi Sumber dan Bahan Belajar di Internet bagi Guru PAUD di Kecamatan Ngaglik, Sleman - Astri Hapsari; Resnia Novitasari; Hepi Wahyuningsih (Jurnal Pengabdian Pada Masyarakat, 2018)
TRAINING OF RESOURCE LITERACY AND LEARNING MATERIALS ON THE INTERNET FOR PAUD TEACHERS IN NGAGLIK DISTRICT, SLEMAN. Learning media and resources are parts of Early Childhood Education instructional design. Nowadays, learning media and resources include not only natural environment but also cyber space in internet. However, some Early Childhood Education teachers are not aware of the potential of using these learning media and resources in their teaching practice. Therefore, an in-house training of learning media and resources literacy was designed for Early Childhood Education teachers in District of Ngaglik, Sleman Regency. This training was attended by Rumah Anak Pintar Islami and Smart Child Al-Mubarok Pre-Schools. The outcome of the training was better understanding on learning media and resources in the internet which the teachers can use in their teaching practice.